A Descriptive Case Study of the Human Rights Due-Diligence Process of a Mining and Exploration Multinational Corporation - Elder, Jon R M (2010)
The success of the contemporary human rights movement is such that the rights they espouse are increasingly relevant to multinational corporations (MNCs), who, commensurate with their influence within the current world order, potentially impact upon all such rights for a wide variety of stakeholders. A recent focus of this contentious field within the global public domain, has been the adoption by the United Nations Human Rights Council, of a framework that confers upon corporations a responsibility to respect human rights by undertaking due-diligence: processes by which a company becomes aware of, and manages its human rights impacts. Despite increasing interest in this area, little research exists regarding how MNCs respond to human rights issues. Therefore, through adopting the research strategy of a descriptive case study, this work examines the human rights due-diligence process of a mining and exploration MNC. A novel finding of this research is that the MNC under examination arguably demonstrates a corporate responsibility to respect human rights, and in doing so, addresses several issues associated with this emerging practice. However, the results also suggest that some human rights issues facing MNCs are likely to persist irrespective of resources devoted to their due-diligence processes, such as those reflective of wider challenges to the foundations of the human rights movement itself. This work concludes by arguing that a possible solution to these problems lies in proactive efforts on the part of MNCs to engage their stakeholders within the public domain, and mediate acceptable solutions to these problems.